Financial Literacy, Financial Behavior, and Financial Attitude Toward Invesment Decision - Masitoh, Noneng; Badriatin, Tine; Rosyadi, Agi; Rahmawati, Mira (Program Studi Perbankan dan Keuangan Fakultas Ekonomi Universitas Siliwangi, 2024)
This research aims to determine and analyze the influence of financial literacy, financial behavior and financial attitudes on investment decisions. The type of research used is quantitative research using descriptive methods. The type and source of data used is primary data, namely data collected and processed by the researcher himself from the object. The total population in this study was 52 people and the sampling technique used was total sampling. Data was collected using a questionnaire method from 52 respondents who were sampled in this study. The data analysis techniques used in this research are descriptive statistical analysis, data quality test, classical assumption test, multiple linear regression test, F test, t test and coefficient of determination with the help of the SPSS version 24 software program. The results of this study show that financial literacy , financial behavior and financial attitudes have a significant influence on investment decisions.